Revitalizing Higher Education Quality through the HESK Model for Integrating Cultural Values and Modern Management Principles - Sahrul (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
Higher education in the era of globalization faces significant challenges in producing graduates who are globally competitive while preserving local cultural values. This study introduces the HESK model, an innovative framework emphasizing Human Skill, Entrepreneurship, Social Effect, and Knowledge Work, to improve the quality of higher education management. Using a 4-D research and development approach, the research focuses on the needs assessment phase conducted at Al-Chaeriyah Mamuju College of Education (STIT). The findings demonstrate that the HESK model effectively addresses gaps in educational services by integrating cultural values with modern management principles. Through its holistic and adaptable approach, the HESK model enhances the quality of services, ensuring alignment with global demands while preserving local identity. This study provides a significant contribution by offering a scalable framework that can be implemented across diverse higher education institutions, fostering a balance between global relevance and local contextualization. The results highlight the model's potential in bridging gaps and meeting contemporary educational challenges effectively.